Determination of the magnetic dipolar moment and magnetization of a permanent neodymium N48 magnet - Urquiaga Vásquez , Ausberto Wilson (2025)
In the present work, the magnetic dipole moment and the magnetization of a neodymium magnet N48 of annular geometry were determined. The magnet was introduced into a stable magnetic field generated by two Helmholtz coils to measure the frequency of oscillation and the magnetic field of the coils. The oscillatory movement of the magnet was filmed with a Samsung S8’s video camera that records at 240 frames per second. The video was analyzed with the Tracker software to calculate the angular frequency. Finally the magnetic dipole moment and magnetization were calculated using empirical formulas. The oscillatory frequency was found to be 18 r/s, the magnetic field resulting from the Helmholtz coils 123.44 uT, the magnetic dipole momentum 2.6 Am2 and the magnetization of the neodymium magnet N48 1.14 x 106 A/m.